Aa - Antwerpen Actueel. (Antwerpen : Koninklijk Museum voor Schone Kunsten, 1970)
Bailleux, Cesar ; Celie, Peter ; Debois, Albert ; De Vos, Rik ; Francis, Filip ; Heyrman, Hugo ; Jacobs, Herman ; Lauwers, Laurent ; Overberghe, Cel ; Panamarenko ; Pauwels, Antoon ; Persoons, Hans ; Pladys, Mon ; Szukalski, Albert ; Vercammen, Wout ; Nieuwe Coloristen
Aa - Antwerpen Actueel, Koninklijk Museum voor Schone Kunsten, Antwerpen, 3.10 t/m 15.11.1970
boek